Development of High-Altitude Hybrid Fan Centrifugal Compressor System for Turbochargers and Utilization of AI to Improve Combustor Performance - Osemwengie, O.; Abdallah, S. A.; Fanegan, J. O. (European Journal of Applied Sciences, 2022)
This opinion paper focus on the belief of the authors, that adding a fan or pre-compression stage in front of a centrifugal impeller typically found in commercial turbochargers has the potential to increase the overall pressure ratio of the turbocharger, which help with high-altitude operation. Additionally, this paper address conviction of the authors that the utilization of artificial intelligence and data science will improve combustor performance. The focus is on the development of high-altitude hybrid fan centrifugal and compressor system for turbochargers. Current attainable flight times of Unmanned Aerial Vehicles (UAVs) at high altitudes greatly hinder potential mission capabilities. Specifically, the US Army’s small UAVs are propelled by automotive compression-ignition (CI) engines, which deliver the required high efficiency and low fuel consumption but lack the ability to ingest an adequate mass flow rate of low-density air into their compression cylinders at high altitudes. A hybrid fan- centrifugal compressor system will be developed and integrated onto these UAV engines to provide the air mass flow rate necessary to operate at 60% of maximum sea-level power while at 30,000 feet altitude; thus, reducing the hindrance of high altitude environmental factors on UAV missions. The combined system will be integrated on a dual shaft to allow for fan and compressor to rotate at different speeds. Dual shafts are, typically, used in turbojet engines for combined fan and axial flow compressors for delivering large air mass flow. This hybrid fan-centrifugal compressor system will offer higher pressure and mass flow rate to the current Army UAV engines than standard turbochargers, while maintaining simplicity and manufacturability.